Bioinspired and Sustainable Chitosan Based Monoliths for Antibody Capture and Release - Barroso, Telma (2017)
The authors would like to thank the financial support from Fundacao para a Ciencia e Tecnologia, Portugal, through contracts MIT-Pt/BS-CTRM/0051/2008, PTDC/EBB-BIO/102163/2008, PTDC/EBB-BIO/098961/2008 and PTDC/EBB-BIO/118317/2010 and doctoral grant SFRH/BD/62475/2009 (T. B.), Bioengineering Systems Focus Area, Fundacao Calouste Gulbenkian, FEDER and FSE. We wish to thank the Analytical Services Laboratory of REQUIMTE for the characterization of materials. Authors are also thankful to Lonza Biologics, UK (Dr Richard Alldread) and the Animal Cell Technology Unit of ITQB-UNL/IBET (Dr Paula M Alves and Dr Ana Teixeira) for providing the cell culture bulks of antibodies.